2018
DOI: 10.12688/wellcomeopenres.14713.1
|View full text |Cite
|
Sign up to set email alerts
|

Proposed classification for interproximal contacts of primary molars using CBCT: a pilot study

Abstract: Contact areas in primary teeth are known to be broader, flatter, Background: and situated more gingivally than in permanent teeth. The objective of the present study was to evaluate the different types of intact contact areas in primary teeth using cone beam computed tomography (CBCT) among children.A cross-sectional study was designed with 74 contacts from 28 Methods: existing CBCT images of patients aged between 3 and 14 years, obtained from the Indian Dental Education Academy, Chennai, India. The shape of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
5
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 4 publications
5
5
3
Order By: Relevance
“…The highest and the least prevalent contact in the mandible, however, was the I (80.5%) type and S (1.9%) type, respectively. Compared with previous studies, 11,12 the results of our study were in perfect agreement with respect to the most common contact but were contradictory with respect to the least common contact which was different in all the three different studies. Overall, the order from the most to the least common contact areas in this study was I (79.7%), X (10.0%), S (6.6%), and O (3.7%), respectively, which was not consistent with the results of previous studies, which reported an order of I > X > O > S 11 and I > S > O > X 12 .…”
Section: Discussioncontrasting
confidence: 61%
See 4 more Smart Citations
“…The highest and the least prevalent contact in the mandible, however, was the I (80.5%) type and S (1.9%) type, respectively. Compared with previous studies, 11,12 the results of our study were in perfect agreement with respect to the most common contact but were contradictory with respect to the least common contact which was different in all the three different studies. Overall, the order from the most to the least common contact areas in this study was I (79.7%), X (10.0%), S (6.6%), and O (3.7%), respectively, which was not consistent with the results of previous studies, which reported an order of I > X > O > S 11 and I > S > O > X 12 .…”
Section: Discussioncontrasting
confidence: 61%
“…Compared with previous studies, 11,12 the results of our study were in perfect agreement with respect to the most common contact but were contradictory with respect to the least common contact which was different in all the three different studies. Overall, the order from the most to the least common contact areas in this study was I (79.7%), X (10.0%), S (6.6%), and O (3.7%), respectively, which was not consistent with the results of previous studies, which reported an order of I > X > O > S 11 and I > S > O > X 12 . These differences in findings could be attributed to the significant difference in the sample size, which consisted of 1,343 contacts in this study compared with 74 contacts performed with CBCT images and 4,476 contacts in the clinical study.…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations